REVIEW OF IMPACT OF ENTREPRENEURSHIP EDUCATION ON THE PERFORMANCE OF SMALL, MEDIUM AND MICRO ENTERPRISES (SMMES) IN RURAL SOUTH AFRICA - Chinaza Uleanya; Ademola Olumuyiwa Omotosho; Bongani Thulani Gamede (Sosio-Didaktika: Social Science Education Journal, 2021)
The future of the economies of various nations across the globe lies in the entrepreneurial trends and activities. Entrepreneurship in this regard is viewed from the activities of Small, Medium and Micro Enterprises (SMMEs). Entrepreneurial activities are also viewed as development driving tool for rural societies. However, necessary skills are needed for such desired goal to be achieved and the education provided by institutions of learning is one by which entrepreneurial expertise can be attained. Conversely, entrepreneurship education is not considered as a major subject receiving due attention in South African institutions of learning. Hence, this study explores the impact of entrepreneurship education on the performance of Small, Medium and Micro Enterprises (SMMEs). Review method was adopted for this study. Thus, relevant literatures were reviewed. The findings of the study amongst others show that relevant skills are needed for entrepreneurial activities to thrive in rural societies and aid the needed development. Also, entrepreneurship education tends to impact entrepreneurial activities. The study therefore recommends amongst others that entrepreneurship education should be promoted in rural based institutions of learning in South Africa taking into cognizance the needs and demands of the communities and its surroundings where the institutions are situated.